2017
DOI: 10.14336/ad.2016.0530
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA H19 Induces Cerebral Ischemia Reperfusion Injury via Activation of Autophagy

Abstract: Long non-coding RNA H19 (lncRNA H19) was found to be upregulated by hypoxia, its expression and function have never been tested in cerebral ischemia and reperfusion (I/R) injury. This study intended to investigate the role of lncRNA H19 and H19 gene variation in cerebral I/R injury with focusing on its relationship with autophagy activation. Cerebral I/R was induced in rats by middle cerebral artery occlusion followed by reperfusion. SH-SY5Y cells were subjected to oxygen and glucose deprivation and reperfusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
149
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(155 citation statements)
references
References 24 publications
6
149
0
Order By: Relevance
“…Together, these data support the concept that TUG1 is associated with cerebral IRI and functions as a positive regulator in IRI progression. A new mechanism has been proposed in which lncRNA H19 induces cerebral ischaemia‐reperfusion injury and more recently, Weixin et al demonstrated that lncRNA MALAT1 inhibits apoptosis induced by oxygen‐glucose deprivation and reoxygenation in human brain microvascular endothelial cells. From these studies, a broader understanding of the mechanisms of action of more lncRNAs may further the development of new therapeutic strategies for cerebral IRI.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these data support the concept that TUG1 is associated with cerebral IRI and functions as a positive regulator in IRI progression. A new mechanism has been proposed in which lncRNA H19 induces cerebral ischaemia‐reperfusion injury and more recently, Weixin et al demonstrated that lncRNA MALAT1 inhibits apoptosis induced by oxygen‐glucose deprivation and reoxygenation in human brain microvascular endothelial cells. From these studies, a broader understanding of the mechanisms of action of more lncRNAs may further the development of new therapeutic strategies for cerebral IRI.…”
Section: Discussionmentioning
confidence: 99%
“…7 Furthermore, lncRNAs C2dat1 and NILR were shown to promote neuronal survival in the ischemic brain by modulating NF-κB signaling and inhibiting p53 signaling, respectively, 37,38 whereas lncRNAs H19 and TUG1 were shown to promote secondary ischemic brain damage by activating autophagy, apoptosis and p53, respectively. 3941 A recent study further demonstrated that lncRNA MALAT1 induced after focal ischemia is neuroprotective by curtailing inflammation and apoptosis. 9 …”
Section: Discussionmentioning
confidence: 99%
“…7 However, the clinical value of H19 as a diagnostic and prognostic marker, as well as its relevance as a potential intervention target for ischemic stroke, requires further investigation.…”
Section: Strokementioning
confidence: 99%
“…3 Polymorphisms of the H19 gene have been demonstrated to alter its expression and are associated with risk factors for cardiovascular and cerebrovascular disease, such as obesity and high blood pressure. [4][5][6][7] H19 is strongly expressed during embryogenesis and subsequently downregulated after birth, but can be reactivated under hypoxic conditions. 8,9 Thus, we hypothesized that H19 might participate in the pathogenesis of ischemic stroke.…”
mentioning
confidence: 99%